2015
DOI: 10.1080/15548627.2015.1009781
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ATG14 by EGR1-MIR152 sensitizes ovarian cancer cells to cisplatin-induced apoptosis by inhibiting cyto-protective autophagy

Abstract: Cisplatin is commonly used in ovarian cancer treatment by inducing apoptosis in cancer cells as a result of lethal DNA damage. However, the intrinsic and acquired resistance to cisplatin in cancer cells remains a big challenge for improving overall survival. The cyto-protective functions of autophagy in cancer cells have been suggested as a potential mechanism for chemoresistance. Here, we reported MIR152 as a new autophagy-regulating miRNA that plays a role in cisplatin-resistance. We showed that MIR152 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 46 publications
5
98
1
Order By: Relevance
“…In these reports, overexpression of miRNAs targeting PTEN has been considered a contributing factor for tumor development (Huse et al, 2009). However, as our study indicated, miR-152 is also a potential regulator of PTEN; most previous reports have indicated that miR-152 acts as a tumor suppressor by targeting proteins other than PTEN (Cheng et al, 2014;He et al, 2015;. Therefore, although our data suggest a protective function of miR-152 during hypoxiainduced apoptosis in primary microvascular endothelial cells, the miR-152-PTEN relationship and its effects on the development and progression of cancer requires further investigation.…”
Section: Discussioncontrasting
confidence: 38%
“…In these reports, overexpression of miRNAs targeting PTEN has been considered a contributing factor for tumor development (Huse et al, 2009). However, as our study indicated, miR-152 is also a potential regulator of PTEN; most previous reports have indicated that miR-152 acts as a tumor suppressor by targeting proteins other than PTEN (Cheng et al, 2014;He et al, 2015;. Therefore, although our data suggest a protective function of miR-152 during hypoxiainduced apoptosis in primary microvascular endothelial cells, the miR-152-PTEN relationship and its effects on the development and progression of cancer requires further investigation.…”
Section: Discussioncontrasting
confidence: 38%
“…Among its related pathways are autophagy pathway and senescence and autophagy in cancer. A recent study has shown that ATG14, a crucial member of ATG gene family, plays a vital role in autophagy processes, [15] which provides protections to cancer cells from the deadly stresses that result from radiation, chemotherapy or other treatments [16]. However, how cancer cells modulate the expression of ATG to prevent cell death caused by radiation and chemotherapy still needs to be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Although autophagy acts as a "double-edged sword" in tumorigenesis (19), autophagy acts more as a cytoprotective mechanism in tumor therapy (20)(21)(22). Many anticancer agents, such as imatinib, cisplatin, vismodegib, and asparaginase, can also induce autophagy in tumor cells, whereas inhibition of autophagy significantly enhances the antitumor efficacies of these agents, indicating that a combination of autophagy inhibitors and antitumor agents could be an efficient therapeutic strategy for malignancy (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%